2016
DOI: 10.1155/2016/6197353
|View full text |Cite
|
Sign up to set email alerts
|

Lack of an Association between Neutrophil-to-Lymphocyte Ratio and PSA Failure of Prostate Cancer Patients Who Underwent Radical Prostatectomy

Abstract: Introduction. The neutrophil-to-lymphocyte ratio (NLR), which can be easily calculated from routine complete blood counts of the peripheral blood, has been suggested to serve as a prognostic factor for some solid malignancies. In the present study, we aimed to determine the relationship between NLR in prostate cancer patients undergoing radical prostatectomy (RP) and their prognosis. Materials and Methods. We assessed NLR in 73 men (patients) who received RP for their prostate cancer. We also performed immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 28 publications
2
19
1
Order By: Relevance
“…When we analyzed PSA values and the histopathological features (perineural invasion, surgical margin positivity, extraprostatic spread, seminal vesicle invasion, and Gleason score) with high NLR, there was a relationship between high NLR and Gleason score. Contrary to our cohort; Maeda and colleagues found no association between NLR and Gleason score and other histopathological features in their study covering 73 patients (20). PLR independently predicts poor prognosis in patients with conditions including gastric cancer, pancreatic cancer, ovarian cancer, colorectal cancer, non-small cell lung cancer, hepatocellular carcinoma, renal cell cancer, and esophageal cancer (16).…”
Section: Discussioncontrasting
confidence: 72%
“…When we analyzed PSA values and the histopathological features (perineural invasion, surgical margin positivity, extraprostatic spread, seminal vesicle invasion, and Gleason score) with high NLR, there was a relationship between high NLR and Gleason score. Contrary to our cohort; Maeda and colleagues found no association between NLR and Gleason score and other histopathological features in their study covering 73 patients (20). PLR independently predicts poor prognosis in patients with conditions including gastric cancer, pancreatic cancer, ovarian cancer, colorectal cancer, non-small cell lung cancer, hepatocellular carcinoma, renal cell cancer, and esophageal cancer (16).…”
Section: Discussioncontrasting
confidence: 72%
“…It has been proposed that the NLR can be used to estimate the magnitude of systemic inflammation in cancer patients [ 13 16 ]. Several retrospective studies have evaluated the baseline NLR as a prognostic factor in prostate cancer [ 17 20 ]. The NLR can easily be calculated from the CBC data without much labor or cost.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, leukocytes were demonstrated to accumulate in the lung prior to infiltration of the tissue by cancer cells (in a pre-metastatic lung), and their numbers increased during metastatic progression (in a metastatic lung) ( 10 ). Increasingly, evidence has demonstrated that a systemic inflammatory response has a prognostic value in various cancers ( 11 14 ). Amongst the convenient and available markers, a high ratio of neutrophils to lymphocytes (NLR) and platelets to lymphocytes (PLR), which are calculated from the complete blood count with differential ( 15 ), also have been combined to form inflammation-based prognostic scores to predict cancer survival ( 11 ).…”
Section: Introductionmentioning
confidence: 99%